2008
DOI: 10.1016/j.fct.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic oral toxicity studies of Se-methylselenocysteine, an organoselenium compound for breast cancer prevention

Abstract: Se-methylselenocysteine (MSC) is an organoselenium compound being developed for breast cancer chemoprevention. To characterize MSC toxicity, CD rats received daily gavage doses of 0, 0.5, 1.0, or 2.0 mg/kg/day (0, 3, 6, or 12 mg/m 2 /day), and beagle dogs received daily gavage doses of 0, 0.15, 0.3, or 0.6 mg/kg/day (0, 3, 6, or 12 mg/m 2 /day) for 28 days. In rats, MSC induced dose-related hepatomegaly in both sexes; mild anemia, thrombocytopenia, and elevated liver enzymes were observed in high dose females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…A subacute toxicity study found that SeMC induced dose-related hepatomegaly and hepatocellular degeneration in rats and dogs after 28-day treatment (Johnson et al, 2008). In agreement, our 90-day subchronic toxicity study demonstrated that the relative liver weight was dose-dependently increased by SeMC in both male and female rats.…”
Section: Discussionsupporting
confidence: 89%
“…A subacute toxicity study found that SeMC induced dose-related hepatomegaly and hepatocellular degeneration in rats and dogs after 28-day treatment (Johnson et al, 2008). In agreement, our 90-day subchronic toxicity study demonstrated that the relative liver weight was dose-dependently increased by SeMC in both male and female rats.…”
Section: Discussionsupporting
confidence: 89%
“…Various organoselenium compounds including methylselenocysteine are known to exert cytotoxic anti-neoplastic properties against mammary adenocarcinoma/carcinoma (Coyne et al, 2011; Ip & Dong 2001; Johnson, Morrissey, Kapetanovic, Crowell, & McCormick 2008; Li et al, 2009; Medina, Thompson, Ganther, & Ip 2001) and other cancer cell types (Cao, Durrani, & Rustum 2004; Chintala et al, 2010) while also enhancing the potency of anthracyclines (Coyne et al, 2011; Juliger, Goenaga-Infante, Lister, Fitzgibbon, & Joel 2007; Li, Zhou, Dong & Ip C 2007; Li, Zhou, Wang, Zhang, Dong, & Ip 2007) and covalent epirubicin-immunochemotherapeutics (Coyne et al, 2011). Somewhat surprisingly the cytotoxic anti-neoplastic potency of griseofulvin against mammary adenocarcinoma (SKBr-3) was substantially greater than molar-equivalent (standardized) concentrations of methylselenocysteine (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Se was first discovered in 1817 in the form of a reddish precipitate, an elemental form of Se (Zhang, 2009). Elemental Se was originally considered to biologically inert in upregulating selenoenzymes and consequently most work has focused on organic forms such as selenomethionine and Se-methylselenocysteine, and on inorganic sodium selenate and selenite (Weekley and Harris, 2013;Schrauzer, 2000;Johnson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%